Televisie opnamen over een 'Gedenksteen voor Marinus van der Lubbe' met o.a. Martin Schouten - Schouten, Martin. (2000)
Televisie opnamen over een 'Gedenksteen voor Marinus van der Lubbe' met o.a. Martin Schouten.